Kepuasan Siswa Terhadap Praktek Magang Mahasiswa Mengajar - Ferida Rahmawati; Muhammad Farrel Feriansyah; Muhamad Shokhihul Islam; Luk Luk Ilmaknun; Tarisa Khali (CV. ULIL ALBAB CORP, 2025)
Student satisfaction in learning is related to teacher practice in teaching. As prospective teachers, students must carry out teaching practices to increase their cognitive, psychomotor and affective abilities. The research aims to determine the description of student satisfaction with the teaching practices carried out by student teachers. This research is a descriptive type of quantitative research—student satisfaction research variables. The research instrument is a questionnaire. The questionnaire consists of 14 questions. The research respondents were students in grades 7 and 9 who were the targets of student learning practices. Respondents numbered 100 students, and the sampling technique was purposive sampling. The oldest student was 15 years old (9%), while the most significant number of students was 12 years old (44%). Most carry out teaching practices to increase their cognitive, psychomotor and affective abilities 52% are female, while 48% are male. The most significant number of students in class 7 is as much as 64%, while class 9 is only 36%. 52% more students were dissatisfied. However, the difference between satisfied and dissatisfied students is almost equal. The results of the research show that the condition of satisfaction based on student's answers to the learning practices carried out by students is almost balanced, which means that there are still 52% of students who say they are not satisfied. Therefore, there is a need to increase students' cognitive, psychomotor and affective abilities in teaching to remember them. as a prospective teacher.